Experience and attitudes of teenagers facing sexuality - Aguiar Lima, Fernanda Cristina; Barbosa de Jesus, Flávia; Baccarat de Godoy Martins, Christine; Pires Salomé de Souza, Solange; Fonseca de Matos, Karla (O Mundo da Saúde, 2013)
Considering early sexual initiation, pregnancy and sexually transmitted diseases in adolescence, it is essential to know how the adolescent experiences his sexuality in order to better guide preventive actions. This study aimed at knowing the attitudes of adolescents regarding sexuality. This is a descriptive study, with 499 high school first-year students. Data were collected by closed questionnaire and analyzed using Epi Info. One hundred ninety boys (38.1%) and 309 girls (61.9%) were surveyed. It was observed that there is little dialogue about sexuality among partners, the sexual initiation happens earlier among boys and the first sexual relation happens with a boyfriend (for girls) and without any commitment (for boys). At the moment, 67.2% of the interviewed teenagers have an active sexual life with casual frequency of 1 to 3 partners for girls in the last three months (72.3%), and 48.1% of the boys do not remember this information. 71.7% of the interviewed stated to be heterosexual. It was concluded that educational practices within the teenagers’ sexuality and the involvement of the family in dialogue and guidance are important.